Quality and Sources of Dietary Carbohydrate Intake and Self-perceived Quality of Life in Middle-aged and Older Adults of the Framingham Heart Offspring Study (P18-081-19). (13th June 2019) - Gayer, Bridget; Sawicki, Caleigh; Jacques, Paul; Livingston, Kara; Hruby, Adela; Rogers, Gail; McKeown, Nicola
Abstract: Objectives: The objective of the present study was to examine the cross-sectional association between carbohydrate quality and intake of carbohydrate-rich food groups with quality of life. Methods: We examined the cross-sectional association between carbohydrate intake and self-reported quality of life among 2414 participants of the Framingham Offspring Study (FOS). Self-reported quality of life was assessed using three summary scores from the SF-36 questionnaire: Physical Component Summary (PCS), Mental Component Summary (MCS), and Physical Function Score (PFS). Cumulative dietary intake from the fifth (1991–1995) and sixth (1995–1998) FOS examinations was used to assess overall dietary carbohydrate quality using the Carbohydrate Quality Index (CQI) as well as intake of five carbohydrate-rich food groups: fruits, vegetables, whole grain (WG), refined grains, and sugar-sweetened beverages (SSB). Multivariable-adjusted mean PCS and MCS, and the odds ratio (OR) of reporting good physical function defined as PFS ≥ 80, were estimated across tertiles of carbohydrate exposures. P for trend was calculated to assess linearity of associations. Results: Higher CQI was significantly associated with a 3% higher mean PCS score after adjustment for demographic and lifestyle factors, and independent of high cholesterol, hypertension, diabetes, and other aspects of diet ( P trend = 0.0003). Furthermore, our results showed a higher odds of having good PFS in the highest CQI tertile [OR (95% CI) 1.9 (1.5–2.5); P trend < 0.0001]. No association was observed between CQI and MCS. After adjustment for other aspects of diet, fruit and vegetable intake were positively associated with PCS and with odds of having good PFS, while an inverse association was observed between SSB intake and PCS. A nominal significant positive relationship was observed between WG intake and PCS (P-trend = 0.06) after adjustment for other aspects of diet, fruit and vegetable intake. Refined grain intake was not associated with any quality of life measures. Conclusions: Overall carbohydrate quality, as well as specific carbohydrate-rich food sources including fruits, vegetables, and WG, are associated with higher self-reported physical quality of life measures. Funding Sources: This work is supported by the General Mills Bell Institute of Health and Nutrition and USDA ARS agreement No. 58-1950-4-003.